Translanguaging in Conjunction with language revitalization. (August 2020) - Seals, Corinne A.; Olsen-Reeder, Vincent
Abstract: Research into sustainable translanguaging has begun to address teacher and community concern around the use of translanguaging practices in the quest to revitalize and maintain vulnerable languages. The current article adds to this discussion through an empirical examination of translanguaging practices in te reo Māori and Samoan early childhood educational environments in New Zealand. Both communities have valid concerns and face their own challenges regarding protecting the vitality of these languages, and this has a major impact upon the work that we need to do to ensure we are making use of socially responsive translanguaging to support language revitalization and maintenance efforts. The current article presents results of our school-based ethnographies with Māori and Samoan communities in the Wellington region of New Zealand 2017–2019, as well as the pedagogical translanguaging rules that we developed based on this research. We first present our findings of spontaneous translanguaging within these educational spaces. Then, we explain how we applied these findings to the creation of translingual teaching materials for these spaces. Finally, we discuss how these resources contribute to a socially responsive translanguaging pedagogy and the importance of this for marginalized communities.